ChemInform Abstract: Domino Access to Yne‐Functionalized Benzoisoindolines from Triynes. Issue 50 (16th December 2014) - Li, Lidong; Hu, Qiong; Zhou, Pingping; Xie, Haifeng; Zhang, Xiaorong; Zhang, Hao; Wang, Hua; Hu, Yimin
Abstract A Cu(I)‐catalyzed regioselective [4 + 2]‐type cycloaddition reaction leading to yne‐functionalized benzoisoindoles is presented.